Correlation analysis of ApoB and TyG index levels with residual cardiovascular risk in patients with acute myocardial infarction - Wang, Yuanyuan; Guo, Dachuan; Wang, Youzhi; Yang, Jianmin; Li, Peng (Frontiers in Endocrinology, 2025)
BackgroundLow-density lipoprotein cholesterol (LDL-C) has now been the primary target for lipid-lowering therapy in the European and US guidelines for the management of dyslipidemia, with increasing interest in apolipoprotein B (ApoB) as a secondary target. The relationship between ApoB and the severity of acute myocardial infarction as well as residual risk still needs to be further determined. Coronary atherosclerosis occurs as a result of a complex set of factors, and there is a strong relationship between insulin resistance and cardiovascular disease. In contrast, there are limited studies on the relationship between TyG index (triglyceride glucose index), an indicator of insulin resistance, and cardiovascular disease. The purpose of this study was to investigate the value of ApoB and TyG index in assessing the severity of myocardial infarction and predicting prognosis.MethodsThis study included 712 participants with acute myocardial infarction for a 5-year follow-up. Spearman correlation analysis and generalized linear model analysis were used to assess the correlation between ApoB and the severity of coronary atherosclerosis. Risk regression analysis was used to assess the correlation between ApoB and residual risk in patients with acute myocardial infarction, and the C-statistic, net reclassification index (NRI), and integrated discriminant improvement index (IDI) were further calculated to assess the predictive value of ApoB for residual risk after myocardial infarction.ResultsCategorizing apoB, LDL-C, and TyG indices according to tertiles, higher levels of ApoB were significantly associated with the severity of coronary artery stenosis in patients with acute myocardial infarction (P<0.001), whereas no such associations were found for elevated levels of LDL-C and TyG indices (P >0.05). Higher levels of apoB were significantly associated with residual risk of coronary atherosclerotic heart disease after full adjustment for confounders. Higher levels of ApoB were significantly associated with residual risk of coronary atherosclerotic heart disease by binary logistic regression analysis after complete adjustment for confounders. In multivariate variable-adjusted models, the OR and 95% CI for intermediate levels of ApoB (0.85-1.05 g/L) compared with low levels of ApoB (≤0.84 g/L) and residual risk after myocardial infarction was 2.06 (1.11, 3.81) (P<0.05), and for high levels of ApoB (≥1.06 g/L) the OR and 95% CI was 2.60 (1.29, 5.26) (P < 0.05); for each SD increase in ApoB level, the increase in residual risk after myocardial infarction would increase 4.75-fold (P = 0.001). Higher levels of TyG index were not found to be significantly associated with residual risk after myocardial infarction (P > 0.05). The inclusion of LDL-C, ApoB, and TyG indices in the constructed baseline risk model, and ApoB significantly improved the predictive ability of the traditional risk model for residual risk. The ROC curve of the baseline risk model showed an AUC of 0.649; the AUC after adding LDL-C to the model was 0.680 (P=0.05684); the AUC after adding TyG to the model was 0.663 (P=0.1635); and the addition of ApoB to the baseline model increased the AUC substantially to 0.702 (P= 0.00417). Inclusion of ApoB in the baseline risk model improved the prediction of MACE most significantly in the baseline model (net reclassification index [NRI]: 0.3324, P < 0.001; integrated discriminant improvement index [IDI]: 0.0414, P < 0.001); with the inclusion of LDL-C the NRI was 0.3218 (P < 0.001), and IDI was 0.0263 (P < 0.001); NRI after inclusion of TyG index was 0.2169 (P = 0.017); IDI was 0.0082 (P = 0.022).ConclusionsApoB is an independent risk factor for major adverse cardiovascular events (MACE) following myocardial infarction. Elevated ApoB levels are more advantageous than elevated LDL-C levels in assessing the severity of coronary artery stenosis in myocardial infarction patients and predicting residual risk after myocardial infarction. Therefore, in patients with acute myocardial infarction, ApoB can be considered to guide further intensive treatment. However, the TyG index did not demonstrate a significant advantage in predicting cardiovascular residual risk in this study.